PENGARUH KEPEMILIKAN MANAJERIAL PADA AGENCY COST PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2012 - Lestari Dewi, Ni Luh Gede Emy; Ardiana,SE., MM., M.Acc & Fin., Ak., Putu Agus (E-Jurnal Akuntansi, 2014)
The appointment of managers by shareholders is to maximize shareholder wealth, on the other hand the manager has a different purpose, namely to maximize the welfare of the managers themselves. The goal difference lead to agency conflicts and would also cause the cost of the so-called agency costs. This study aims to determine the effect of managerial ownership on agency cost and agency cost difference between a company that is managed by the owner and by the manager-owner nonmanagers on companies listed in Indonesia Stock Exchange. The results of multiple regression analysis using test and independent t-test found that the higher the managerial ownership, the higher the agency costs but relations between the two variables is not linear but quadratic or parabolic. Other results show that agency costs occur in a company managed by a manager who is also the owner's status as significantly higher than manager-managed company that is not the status of the owner.
Keywords: managerial ownership, agency cost